Problematic, severe asthma in children: a new concept and how to manage it - BUSH, Andrew (Acta medica Lituanica, 2010)
Most children with asthma respond to low doses of inhaled corticosteroids, but a few remain symptomatic despite being prescribed the routine usual asthma medications. The first steps are to ensure that the diagnosis is correct and that the inhaled medications are being given regularly with an appropriately used device. If the children continue to be symptomatic, with any or all of chronic symptoms, acute exacerbations, the need for regular oral corticosteroids, or persistent airflow limitation, then they are considered to have problematic, severe asthma. The next step is to perform a detailed evaluation, including a nurse-lead home visit, to determine whether the child has difficult to treat asthma which improves if the basics are got right, or severe, therapy-resistant asthma; the latter group would be candidates for cytokine-specific therapies. If severe, therapy-resistant asthma is the likely issue, then a detailed invasive investigation is performed, including bronchoscopy, bronchoalveolar lavage and endobronchial biopsy, and trial of adherence with a single intramuscular injection of depot triamcinolone. After detailed phenotyping, an individualised treatment plan is determined. Future work will determine the roles of proximal and distal inflammation, as well as the relative importance of intramural (mucosal) and intraluminal infection. The stability of paediatric asthma phenotypes over time is more variable than those of adults, and the implications of a change of phenotype are yet to be determined. Keywords: steroid resistance, allergen exposure, passive smoking, omalizumab, prednisolone, steroid-sparing agent, phenotype, nitric oxide, induced sputum, endobronchial biopsy